Quality of Experience for Large Ultra-High-Resolution Tiled Displays with Synchronization Mismatch. (8th March 2011) - Deshpande Deshpande, Sachin Sachin; Daly Daly, Scott Scott
Abstract : This paper relates to quality of experience when viewing images, video, or other content on large ultra-high-resolution displays made from individual display tiles. We define experiments to measure vernier acuity caused by synchronization mismatch for moving images. The experiments are used to obtain synchronization mismatch acuity threshold as a function of object velocity and as a function of occlusion or gap width. Our main motivation for measuring the synchronization mismatch vernier acuity is its relevance in the application of tiled display systems, which create a single contiguous image using individual discrete panels arranged in a matrix with each panel utilizing a distributed synchronization algorithm to display parts of the overall image. We also propose a subjective assessment method for perception evaluation of synchronization mismatch for large ultra-high-resolution tiled displays. For this, we design a synchronization mismatch measurement test video set for various tile configurations for various interpanel synchronization mismatch values. The proposed method for synchronization mismatch perception can evaluate tiled displays with or without tile bezels. The results from this work can help during design of low-cost tiled display systems, which utilize distributed synchronization mechanisms for a contiguous or bezeled image display.